The Effect of Brand Personality and Customer Satisfaction to Customer Loyalty at The Mall: A Study Case - Tiurida Lily Anita (AIBPM Publisher, 2019)
Visiting a mall nowadays become popular activities that many people do to entertain themselves, family or friends. With so many malls around, each visitor must have one favorite mall he or she preferred to go to. Some customer preferred to go to one mall and other customer preferred other mall. This study aims to analyzed if the customer loyalty to a preferred mall was because the effect of the mall’s brand personality and customer satisfaction. The study took place at Botani Square Shopping Mall, Bogor City. Method analysis used on this study is a multiple regression analysis. The Result of this study conclude that the study of the effect of Brand personality and Customer Satisfaction to Customer Loyalty clearly shows that brand personality and customer satisfaction have an influence on customer loyalty to visit Botani Square Shopping Mall, Bogor City. Keywords: Brand Personality, Customer Satisfaction, Customer Loyalty